2012
DOI: 10.1166/jnn.2012.5621
|View full text |Cite
|
Sign up to set email alerts
|

Electroplating Characteristics of Eutectic Sn–Cu Ions for Micro-Solder Bump on a Si Chip

Abstract: The fabrication of fine bumps on a Si chip is an important issue due to the trend of smaller sized and multi-functioning electronics. In this study, a Sn-Cu near eutectic solder bump was fabricated by electroplating. A Si wafer was used as a substrate, while layers of the Under Bump Metallization (UBM) of Al/Cu/Ni/Au (400/300/400/20 nm in each) were coated onto the Si wafer by electron beam evaporation. The bumps on the UBM were plated by a direct current, and the bump size was 20 x 20 x 10 microm with a 50 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The highest and widest points of each bump measured by the i-Solution program were considered to be the width and height of the bump. The uniformity was calculated using the relation: [100-(Std/Ave) × 100 (%)] [27], where Std represents the standard deviation from the mean bump height and Ave indicates the mean bump height.…”
Section: Methodsmentioning
confidence: 99%
“…The highest and widest points of each bump measured by the i-Solution program were considered to be the width and height of the bump. The uniformity was calculated using the relation: [100-(Std/Ave) × 100 (%)] [27], where Std represents the standard deviation from the mean bump height and Ave indicates the mean bump height.…”
Section: Methodsmentioning
confidence: 99%
“…For all the bumps, the bump height and width increased with increased plating time, as shown in Figure 18a and b respectively. Similarly, in Sn-Cu bumping, by electroplating in the condition of 2.5 A/dm 2 for 10 min, bumps 20 × 20 × 10 µm 3 in size with 50 µm of bump pitch were formed [84]. A near eutectic Sn-0.72 wt % Cu bump was produced in the plating condition of a reduction current density of 1 A/dm 2 for 23 min.…”
Section: Solder Bump By Electroplatingmentioning
confidence: 99%
“…In Sn-3.5Ag bumping, using Equation ( 9), Jun et al [83] reported the cathodic current efficiency (ε) for the Sn-3.5Ag bump as 45.05% [Ec = 0.04358494 g/C, i = 30 mA/cm 2 , ρ = 7.412 g/cm 3 for Sn-3.5Ag]. Park et al [84] studied the Sn-Cu solder bump height variation by increasing the deposition time from 1 to 35 min for a current density ranging from 1 to 5 A/dm 2 . The plating rate of the near-eutectic Sn-Cu bump increased linearly from 0.27 to 2.28 µm/min by increasing the current density from 1 to 5 A/dm 2 .…”
Section: Solder Bump By Electroplatingmentioning
confidence: 99%
See 1 more Smart Citation
“…As for 3D packaging, the higher density of patterns and the more complex circuit lead to the inevitable requirement of electrodeposition for solder bump fabrication. 2,3 Compared to the other solder bump preparation methods including solder preform 4 and sputtering, 5 electroplating has outstanding advantages such as high deposition rate, controllable micro-pattern formation, cost-effective and less time-consuming. As a result, electroplating is recommended as a practical and promising technology for solder bump manufacturing.…”
mentioning
confidence: 99%